2014
DOI: 10.7813/2075-4124.2014/6-3/b.21
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum depression in Malaysian women: the association with the timing of pregnancy and sense of personal control during childbirth

Abstract: Objective: To determine the prevalence of postpartum depression (PPD) in Malaysian women and its association with unplanned pregnancy and experience of control during childbirth. Methods: A cross-sectional study involving women 24-48 hours after delivery. PPD was measured with the Edinburg Postpartum Depression Scale and the timing of pregnancy was assessed with a four question scale. Sense of personal control during childbirth was measured with the Labour Agentry Scale. Other relevant clinical and demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Earlier studies argued that depression is one of the most significant predictors of premature pregnancy and can be moderated by other sociodemographic traits [ 39 ]. However, few studies found that postpartum depression is also related to marital status as four out of nine (44.4 per cent) single women exhibited depression [ 40 ]. Furthermore, Räisänen et al [ 41 ] argue that there is a double risk for mental problems with unintended pregnancies among unmarried women because of low support from family and society.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies argued that depression is one of the most significant predictors of premature pregnancy and can be moderated by other sociodemographic traits [ 39 ]. However, few studies found that postpartum depression is also related to marital status as four out of nine (44.4 per cent) single women exhibited depression [ 40 ]. Furthermore, Räisänen et al [ 41 ] argue that there is a double risk for mental problems with unintended pregnancies among unmarried women because of low support from family and society.…”
Section: Discussionmentioning
confidence: 99%
“…3 PPD is a significant health issue that can impact the health of the mother, her marital relationship, interaction with the newborn as well as infant growth. 5 Although the prevalence of PPD and general depression is between 10% and 15% in the first 3 months of post partum, an increasing trend in prevalence was observed after 3 months until 12 months of post partum and no difference in prevalence was observed through self-reports or clinical interviews. 6 Hence, depression at this critical period of life carries special meanings and consequences to the mother and her relationship with her baby.…”
Section: Open Accessmentioning
confidence: 91%
“…The validity and reliability of the Malay version of EPDS were confirmed by Mahmud et al [34], with the internal consistency designated at 0.86. The EPDS cut-off point was calculated as 12, where mothers who had scored more than 12 were considered to have a higher degree of depressive symptoms [34,35]. The author obtained the original translated questionnaire from Arifin et al [35] and used the tools with Arifin's permission.…”
Section: Edinburgh Postpartum Depression Scalementioning
confidence: 99%
“…The EPDS cut-off point was calculated as 12, where mothers who had scored more than 12 were considered to have a higher degree of depressive symptoms [34,35]. The author obtained the original translated questionnaire from Arifin et al [35] and used the tools with Arifin's permission.…”
Section: Edinburgh Postpartum Depression Scalementioning
confidence: 99%